2021
DOI: 10.1021/acs.analchem.1c02436
|View full text |Cite
|
Sign up to set email alerts
|

Novel Self-Calibrating Amperometric and Ratiometric Electrochemical Nanotip Microsensor for pH Measurement in Rat Brain

Abstract: Brain pH has been proven to be a key factor in maintaining normal brain function. The relationship between local pH fluctuation and brain disease has not been extensively studied due to lack of the accurate in situ analysis technology. Herein, we have for the first time proposed a voltammetric pH sensor by measuring the ratio of current signals instead of the previously reported potential based on the Nernst equation. Single-walled carbon nanotubes (CNT) were first self-assembled on the electrode surface of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…33,34 pH also serves as an indicator of TBI, whereby a reduction of pH is observed because of disrupted anaerobic metabolism and increased acetic acid. 35 To date, several approaches have been developed to follow the progress of brain diseases for brain pH monitoring, including fluorescence spectroscopy, 36,37 electrochemical sensing, 38 and colorimetric sensing. 39 In this study, the determination of pH in aCSF is based on the colorimetric property of a pH sensing film at the fiber tip.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…33,34 pH also serves as an indicator of TBI, whereby a reduction of pH is observed because of disrupted anaerobic metabolism and increased acetic acid. 35 To date, several approaches have been developed to follow the progress of brain diseases for brain pH monitoring, including fluorescence spectroscopy, 36,37 electrochemical sensing, 38 and colorimetric sensing. 39 In this study, the determination of pH in aCSF is based on the colorimetric property of a pH sensing film at the fiber tip.…”
Section: Articlementioning
confidence: 99%
“…These characterization studies on the designed optical sensors have demonstrated good sensing performance of the sensors for brain pH, temperature, DO, and glucose sensing. Compared with commercially available devices for brain monitoring (MRI, MD) or the state-of-the-art EC sensors, 14,38,40 the proposed multiplexed sensing sensors achieved comparable sensitivity, reversibility, stability, and selectivity. In terms of implantable diagnosis, optical sensors could also provide battery-free and remote sensing, and they can be easily miniaturized.…”
Section: Performances Of the Optical Fiber Glucose Sensormentioning
confidence: 99%
“…An electrochemical method with high selectivity can easily realize the real-time and continuous measurement of tissue amino acids, reactive oxygen species (ROS) and neurotransmitters. [14][15][16][17][18] Considering the advantages of electrochemical methods, a reliable Tyr electrochemical sensor is desirable to deeply distinguish and understand the differences of Tyr in normal and pathological environments. However, as far as we know, no electrochemical sensor has been developed for the determination of Tyr in a brain-related biological environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, ratiometric designs necessitate the separate mixing of multiple components, which complicates the manufacturing process. The development of single-component ratiometric sensors has been performed for this purpose. Tian et al, for example, designed and synthesized Hemin-Fc, which consisted of an amide bond connecting a hemin group to two aminoferrocene molecules. The hemin group acts as a recognition unit for O 2 , and the Fc group can act as an internal reference for ratiometric biosensing since its current and potential signals remain nearly constant with variations in O 2 , thereby providing an in-built correction .…”
mentioning
confidence: 99%
“…The hemin group acts as a recognition unit for O 2 , and the Fc group can act as an internal reference for ratiometric biosensing since its current and potential signals remain nearly constant with variations in O 2 , thereby providing an in-built correction . Recently, our group developed a ratiometric electrochemical sensor for in situ pH detection; in this sensor, pH-responsive poly- o -phenylenediamine molecules were deposited via in situ electrochemical polymerization without the use of a reference molecule. Using the electrochemical latent redox ratiometric probes NABFC and ABFC, Manibalan et al developed a novel electrochemical assay platform for monitoring H 2 S production in real-time by living cells ( E. coli ) .…”
mentioning
confidence: 99%